LVAD Use in the Treatment of End-Stage Heart Failure - Todurov, B. M.; Kovtun, H. I.; Shpachuk, A. O.; Kuzmich, I. N.; Druzhina, A. N.; Sudakevich, S. N.; Melnik, A. Y. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Circulatory failure, developing at a certain stage of the course of most heart diseases, is a progressive process, associated with high morbidity and mortality. The effectiveness of generally accepted conservative and resynchronizing therapy for disease progression is relatively low. Mortality of patients with clinically severe congestive heart failure (CHF) reaches 26-29% within a one year after diagnosis. Thus, heart transplantation is the main option for patients with endstage heart failure. About 5,000 heart transplants are performed annually in the world, with 95% of them occurring in North America and Western Europe. But even in countries with a high level of transplantation activity, donor organs of the required quality are still sorely lacking. In such a situation, the main alternative to transplantation may be the use of artificial heart ventricles usually called as ventricular assist device (VAD). In the long run, VAD therapy can serve as a tool for healing (“bridge to recovery”), as a tool of awaiting of further transplantation (“bridge to transplantation”), or as a destination therapy. The article presents the experience of using VAD (in the form of left ventricular bypass) in five patients with end-stage CHF. In order to replace the function of the heart LV, a miniature implant system for auxiliary blood circulation INCOR VAD (Berlin Heart GmbH, Berlin, Germany) was used. Our experience from 5 cases has successfully demonstrated that the implantation of a system for long-term mechanical support of the heart to patients with progressive heart failure can be an effective method of treatment that can safely extend the waiting time for heart transplantation.